某型全自动铆接机刺铆压扁机构凸轮的改进设计 - 陈旭东 (Jixie chuandong)
The cam for thorn riveting and flattening mechanism in automatic riveting machine is the key to decide the quality of electrolytic capacitors.Taking riveting machine of full-automatic riveting/winding assembling appliance,Through motion simulation for its 3D model in Inventor,it is found that the original cam motion performance is conform to the law of quadratic polynomial,the vibration and shock of riveting machine has impact on product processing quality.Based on the quintic polynomial,the improvement of this mechanism is carried out,the motion law of cam oscillating bar is changed.Experiments show that through optimization,the precision and stability of riveting machine is improved.The quality of aluminum electrolytic capacitor becomes better.